SISTEM PENJUALAN AIR ISI ULANG MENGGUNAKAN ARDUINO BERBASIS INTERNET OF THINGS (IOT) - Ajeng Rohamtun Nazilah; Kussigit Santosa (CV. Multi Kreasi Media, 2024)
Pisangan Jaya Village Office is a Government agency in Pisangan Jaya Village, Sepatan District, Tangerang Regency. Making correspondence is one of the services carried out by the Pisangan Jaya Village Government to the community. So far, the process of making letters is still carried out manually, people come to the Village Office to take care of the certificate and verification by officers. Many times people need to repeatedly go to the Village Office due to lack of some requirements. Limited office service hours, making this service less effective and efficient. The goal is to build a web-based correspondence service information system. This information system design process will use prototyping methods to build and implement an administrative service information system at the Pisangan Jaya Village office. This system is able to facilitate village office officers in carrying out mail services, shortening work time, the community is able to make letters easily and.